2018
DOI: 10.2478/hukin-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Relative Age Effect and Long-Term Success in the Spanish Soccer and Basketball National Teams

Abstract: The aims of this study were: i) to analyze whether relative age effect occurs in the athletes of the junior national teams and professional athletes in Spain in general and in soccer and basketball, and ii) to compare the long-term success of the players selected for the junior national team between these sports. The samples for this study were Spanish professional soccer (n = 461) and basketball (n = 250) players in the 2013-2014 premier league and players from the junior Spanish soccer (i.e., n = 273; U-17: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
2
18
1
4
Order By: Relevance
“…In this study, the IDs ranged from 1.34 to 2.69 underlined the presence of RAE in all considered team sports. Thus, the present results showed a different pattern in senior Italian context compared to International ones, where RAE was small or negligible as observed in basketball (Delorme et al, 2009; Werneck et al, 2016; López de Subijana and Lorenzo, 2018), rugby league (Till et al, 2010), volleyball (Campos et al, 2016) and water polo at senior level (Barrenetxea-Garcia et al, 2018). On the other hand, it possible that the proportion of players with less than 18 years (overall mean = 12%) in analyzed teams may partially influence the results contradicting previous results in senior teams and in accordance with other studies which describe RAE in European National Teams (Arrieta et al, 2016).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In this study, the IDs ranged from 1.34 to 2.69 underlined the presence of RAE in all considered team sports. Thus, the present results showed a different pattern in senior Italian context compared to International ones, where RAE was small or negligible as observed in basketball (Delorme et al, 2009; Werneck et al, 2016; López de Subijana and Lorenzo, 2018), rugby league (Till et al, 2010), volleyball (Campos et al, 2016) and water polo at senior level (Barrenetxea-Garcia et al, 2018). On the other hand, it possible that the proportion of players with less than 18 years (overall mean = 12%) in analyzed teams may partially influence the results contradicting previous results in senior teams and in accordance with other studies which describe RAE in European National Teams (Arrieta et al, 2016).…”
Section: Discussioncontrasting
confidence: 64%
“…Despite the pervasiveness of RAE in youth sport teams, controversial results were found at senior professional level (Delorme et al, 2009; Romann et al, 2018). For example, large RAE was found in soccer (Gonzalez-Villora et al, 2015; Brustio et al, 2018), while small or negligible RAE was observed in other sport teams such rugby league (Delorme et al, 2009; Till et al, 2010; Jones et al, 2018), basketball (Delorme et al, 2009; Werneck et al, 2016; López de Subijana and Lorenzo, 2018), volleyball (Campos et al, 2016) and water polo (Barrenetxea-Garcia et al, 2018). A discrepancy in RAE at senior professional level may also emerge in relation to the countrywide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is still a high probability that players included in the sample can still make their senior national team debut, it was not considered in this study. However, looking at the roughly 40% of players who were reselection until age 20, it is very similar to the junior-to-senior reselection seen in various sports, including basketball López de Subijana & Lorenzo, 2018;Wrang et al, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…The analysis confirmed that the RAE had an impact in most sports, both on an individual level and on a team level: for every two subjects born in the last quartile of an age group, more than three of the first quartile of the same age group participated in the same sporting context. The RAE appears to have a large impact on the selection processes associated with TID systems in team sports such as ice hockey [10], basketball [11,12], football [13][14][15], rugby [16], Australian football [17], and handball [18,19]. However, recent research in women´s sports has reported more diverse findings, and the impact of the RAE in these seems to be less extensive [20].…”
Section: Introductionmentioning
confidence: 99%